Board of Commissioners Effectiveness, Transparency, Shari'ah Supervisory Board, and Financial Performance of Indonesian Shari'ah Banks - Saiful; Delli Yanti (UNIB Press, 2024)
This study aims to provide empirical evidence of the Effect of Board of Commissioners' Effectiveness and Risk Transparency on Performance with the Sharia Supervisory Board as Moderating Variable. Performance is measured using the Return On Assets (ROA) ratio. The effectiveness of the Board of Commissioners and the Sharia Supervisory Board in this study was measured by the Score Index Item. Risk transparency is measured using a dummy variable. The sample used in this study was a Sharia Commercial Bank company registered with the Financial Services Authority in 2015-2019 with a total sample of 70 observations. The results of the study indicate that the effectiveness of the board of commissioners has no effect on performance. Risk transparency has a positive effect on performance. The sharia supervisory board is not able to moderate the effect of the effectiveness of the board of commissioners and risk transparency on bank performance